Back at home: the ambassadors conference as an interstitial practice. Issue 4 (20th October 2019) - Kuru, Deniz
ABSTRACT: This article focuses on the novel phenomenon of ambassadors conference, an annual gathering for diplomats stationed abroad who meet back at home at their foreign ministry headquarters. Using the new "practical turn" in diplomatic studies and International Relations in order to focus on this recent and still unstudied aspect of diplomacy, I explain how it presents an interstitial practice in terms of its short duration and different location. Ambassadors conferences' emergence as a setting with both national and international aspects generates new challenges and possibilities for diplomats. After elaborating the common practices related to these gatherings and the way they were institutionalized, I turn in more detail to the case of Turkish ambassadors conferences, showing how they can be employed by the ministry as a means to change the domestic public's perceptions of Turkish diplomats. The conclusion emphasizes how this novel practice can be seen as foreign ministries' answer to globalization.